The Role of ESG Reporting and Digital Technology in Improving Financial Transparency and Corporate Environmental Reputation - Judijanto, Loso; OLAYEMI, Adedayo Ezekiel; ADEKANMBI, Ayodele John (West Science Nature and Technology, 2025)
This study investigates the role of Environmental, Social, and Governance (ESG) reporting and digital technology in enhancing financial transparency and strengthening the environmental reputation of Indonesian corporations. Using a quantitative research design, data were collected from 85 corporate respondents through a structured questionnaire employing a five-point Likert scale. The data were analyzed using SPSS version 25 with multiple regression and mediation analysis techniques. The results indicate that ESG reporting has a significant positive effect on financial transparency and environmental reputation. Digital technology adoption also significantly improves financial transparency and environmental reputation. Furthermore, financial transparency is found to partially mediate the relationship between ESG reporting and environmental reputation, as well as between digital technology and environmental reputation. These findings demonstrate that ESG reporting and digital technology function as complementary mechanisms that enhance transparency and reputational outcomes. The study provides empirical evidence supporting the strategic integration of ESG disclosures and digital transformation to promote sustainable, transparent, and reputable corporate practices in emerging economies such as Indonesia.